Two Pink Lines: An Exploratory, Comparative Study of Florida’s Pregnancy-associated and Nonpregnancy-associated Intimate Partner Homicides - Spence, Sonya (Homicide studies, 2023)
Pregnancy-associated Intimate Partner Homicides (PAIPHs) are murders of pregnant women by a former or current intimate partner. This study uses aggregated public data from 2000 to 2019 to examine 33 Florida Pregnancy-associated Intimate Partner Homicides and a comparison group of 33 Nonpregnant Intimate Partner Homicides (NIPHs). Findings show that unwanted pregnancies or relationships, avoidance of prosecution, doubts concerning the unborn child’s paternity, infidelity accusations, and the victim’s drug use are risk factors for Florida’s Pregnancy-associated Intimate Partner Homicides. Moreover, findings suggest a need for Maternal Intimate Partner Violence programs, policies, and interventions targeted toward pregnant women and their intimate partners.